2005
DOI: 10.1074/jbc.m412925200
|View full text |Cite
|
Sign up to set email alerts
|

6-Bromo-6-deoxy-l-ascorbic Acid

Abstract: Vitamin C intracellular accumulation is mediated by Na؉ -dependent vitamin C transporters SVCT1 and -2 and dehydroascorbic acid transporters GLUT1 and -3. It is unclear which pathways dominate in vivo. As a new step to resolve this issue, we identified and tested 6-bromo-6-deoxy-L-ascorbic acid as a specific candidate for SVCTs. In high performance liquid chromatography and electron paramagnetic resonance analyses, the reduced compounds ascorbic acid and 6-bromo-6-deoxy-L-ascorbic acid were similar. The oxidiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
44
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(49 citation statements)
references
References 35 publications
2
44
0
Order By: Relevance
“…32,48,49) In the present study we confirmed the limited transfer of IAsA in the rat brain, as observed in mouse brain, 34) indicating the unsuitability of this agent for brain studies in vivo. These observations are consistent with the mechanistic hypothesis of Rumsey et al 33) and Corpe et al 50) that ascorbate analogs modified at C-6, such as 6-…”
Section: Resultssupporting
confidence: 81%
“…32,48,49) In the present study we confirmed the limited transfer of IAsA in the rat brain, as observed in mouse brain, 34) indicating the unsuitability of this agent for brain studies in vivo. These observations are consistent with the mechanistic hypothesis of Rumsey et al 33) and Corpe et al 50) that ascorbate analogs modified at C-6, such as 6-…”
Section: Resultssupporting
confidence: 81%
“…There was a somewhat slower clearance of the radioactivity from the blood when compared to 6-18 FAsA 10-13) and 6-131 IAsA 14,15) studied previously. The accumulation of radioactivity in selected organs was highest in the kidneys>liver>lungs>adre nals>heart at 2 min postinjection and then the radioactivity levels gradually decreased with time, similar to those seen for [6][7][8][9][10][11][12][13][14][15][16][17][18] FAsA and 6-131…”
Section: Resultsmentioning
confidence: 85%
“…Moreover, tumor accumulation in the fibrosarcoma was not significant, also similar to those of [6][7][8][9][10][11][12][13][14][15][16][17][18] FAsA and IAsA. Recent studies have shown that high-grade tumor tissue has reduced capacity to accumulate AsA relative to normal tissue.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations